Alterations in the vaginal microbiota of patients with preterm premature rupture of membranes - Yan, Chunmei; Hong, Fanzhen; Xin, Gang; Duan, Shuhong; Deng, Xiaohui; Xu, Yongping (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Preterm premature rupture of membranes (PPROM) is a common pregnancy complication. Yet, the main cause of PPROM remains poorly understood. In this study, we used 16S rRNA gene sequencing technology to identify the differences in vaginal microbiota between pregnant women with PPROM and those who delivered at term. Methods: Vaginal samples were collected from 48 patients with PPROM and 54 age- and gestational age-matched pregnant women who delivered at term (controls). The vaginal microbiota of the two groups was compared using 16S rRNA gene sequencing of the V3-V4 regions. Results: The vaginal microbial composition of the PPROM group was significantly different from that of the control group. Our results showed that the diversity of vaginal microbiota in patients with PPROM increased compared with controls. The relative abundance of Lactobacillus iners, Gardnerella vaginalis, Prevotella bivia, Ochrobactrum sp., Prevotella timonensis, and Ureaplasma parvum were more abundant in patients with PPROM, while Lactobacillus crispatus and Lactobacillus gasseri were more abundant in controls. Ochrobactrum sp., Prevotella timonensis, and Gardnerella vaginalis, could serve as biomarkers for PPROM. Finally, we proposed several metabolic pathways implicated in PPROM, including PWY-6339, PWY-6992, and PWY-7295. Conclusion: PPROM is characterized by vaginal microbial dysbiosis. The dysbiotic vaginal microbiota signatures in patients with PPROM include a higher bacterial diversity, decreased autochthonous bacteria, and increased pathogenic bacteria. These results may be beneficial for developing biomarkers for screening and early diagnosis of PPROM and may provide effective preventative treatments.